Recent advancement of novel marine fungi derived secondary metabolite fibrinolytic compound FGFC in biomedical applications: a review - Lakshmi Jeevithan; Lakshmi Jeevithan; Xiaozhen Diao; Jiudong Hu; Jeevithan Elango; Jeevithan Elango; Jeevithan Elango; Wenhui Wu; Jose Eduardo Mate Sanchez de Val; Saravanan Rajendran; Thanigaivel Sundaram; Suresh Kumar Rajamani Sekar (Frontiers in Cellular and Infection Microbiology, 2024)
For several decades, products derived from marine natural sources (PMN) have been widely identified for several therapeutic applications due to their rich sources of bioactive sub-stances, unique chemical diversity, biocompatibility and excellent biological activity. For the past 15 years, our research team explored several PMNs, especially fungi fibrinolytic compounds (FGFCs). FGFC is an isoindolone alkaloid derived from marine fungi, also known as staplabin analogs or Stachybotrys microspora triprenyl phenol (SMTP). For instance, our previous studies explored different types of FGFCs such as FGFC 1, 2, 3 and 4 from the marine fungi Stachybotrys longispora FG216 derived metabolites. The derivatives of FGFC are potentially employed in several disease treatments, mainly for stroke, cancer, ischemia, acute kidney injury, inflammation, cerebral infarction, thrombolysis and hemorrhagic activities, etc. Due to the increasing use of FGFCs in pharmaceutical and biomedical applications, it is important to understand the fundamental signaling concept of FGFCs. Hence, for the first time, this review collectively summarizes the background, types, mode of action and biological applications of FGFCs and their current endeavors for future therapies.